Cardiac arrhythmias in pulmonary hypertension: A review of mechanisms, prevalence, clinical significance, and patient functional capacity - Rafałowicz, Adam; Wojciechowska, Urszula, Justyna; Mierzejewski, Jakub; Łuniewski, Bartosz; Macko, Angelika; Olszańska, Monika; Lauko, Kamil, Klaudiusz; Sokół, Aleksandra; Mościszko, Klaudia; Hakało, Dominika (Quality in Sport, 2025)
Introduction: Pulmonary hypertension is a chronic cardiovascular disease defined by a mean pulmonary artery pressure (mPAP) of > 20 mmHg, as measured by right heart catheterization (RHC). Rhythm disturbances are relatively common in this condition and significantly worsen patient prognosis. Elucidating the mechanisms that drive arrhythmia development may help identify therapeutic intervention strategies to enhance patient outcomes. Materials and methods: We performed a literature review of epidemiology, pathogenesis, and clinical impact of cardiac arrhythmias in Pulmonary Arterial Hypertension (PAH) and Chronic Thromboembolic Pulmonary Hypertension (CTEPH), analysing registry data, histopathological and electrophysiological studies, and clinical outcomes. Results: Supraventricular arrhythmias (SVA) occur in 10–33 % of patients, rising to 30 % over 10 years. Key mechanisms include atrial stretch and fibrosis, autonomic imbalance, and right ventricular ischemia. Arrhythmias correlate with reduced cardiac output, impaired exercise capacity, and increased mortality. Conclusions: Early detection and maintenance of sinus rhythm enhance survival and functional capacity, highlighting the necessity of research and interventions directed at atrial remodelling, neurohormonal modulation and myocardial ischaemia.